What Role for Store‐Operated Ca2+ Entry in Muscle?. (10th May 2013) - Trebak, Mohamed; Zhang, Wei; Ruhle, Brian; Henkel, Matthew M.; González‐Cobos, José C.; Motiani, Rajender K.; Stolwijk, Judith A.; Newton, Rachel L.; Zhang, Xuexin
Abstract Store‐operated Ca2+ entry (SOCE) is a receptor‐regulated Ca2+ entry pathway that is both ubiquitous and evolutionarily conserved. SOCE is activated by depletion of intracellular Ca2+ stores through receptor‐mediated production of inositol 1, 4, 5‐trisphosphate (IP3). The depletion of endoplasmic reticulum (ER) Ca2+ is sensed by stromal interaction molecule 1 (STIM1). On store depletion, STIM1 aggregates and moves to areas where the ER comes close to the plasma membrane (PM; within 25 nm) to interact with Orai1 channels and activate Ca2+ entry. Ca2+ entry through store‐operated Ca2+ (SOC) channels, originally thought to mediate the replenishment of Ca2+ stores, participate in active downstream signaling by coupling to the activation of enzymes and transcription factors that control a wide variety of long‐term cell functions such as proliferation, growth, and migration. SOCE has also been proposed to contribute to short‐term cellular responses such as muscle contractility. While there are significant STIM1/Orai1 protein levels and SOCE activity in adult skeletal muscle, the precise role of SOCE in skeletal muscle contractility is not clear. The dependence on SOCE during cardiac and smooth muscle contractility is even less certain. Here, we will hypothesize on the contribution of SOCE in muscle and its potential role in contractility and signaling.